2007
DOI: 10.1074/jbc.m607694200
|View full text |Cite
|
Sign up to set email alerts
|

Autoprocessing of Helicobacter pylori γ-Glutamyltranspeptidase Leads to the Formation of a Threonine-Threonine Catalytic Dyad

Abstract: Helicobacter pylorigamma-glutamyltranspeptidase (HpGT) is a glutathione-degrading enzyme that has been shown to be a virulence factor in infection. It is expressed as a 60-kDa inactive precursor that must undergo autocatalytic processing to generate a 40-kDa/20-kDa heterodimer with full gamma-glutamyl amide bond hydrolase activity. The new N terminus of the processed enzyme, Thr-380, is the catalytic nucleophile in both the autoprocessing and enzymatic reactions, indicating that HpGT is a member of the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 35 publications
2
87
0
Order By: Relevance
“…1) (13, 14). Affinity labeling and structural studies of bacterial GGTs revealed that the threonine at the N terminus of the small subunit acts as the catalytic nucleophile in Escherichia coli and Helicobacter pylori GGT (15,16). Using mass spectrometry analysis of inhibitor-bound hGGT1, Castonguay et al (17) identified Thr-381 as the catalytic nucleophile in the human enzyme.…”
mentioning
confidence: 99%
“…1) (13, 14). Affinity labeling and structural studies of bacterial GGTs revealed that the threonine at the N terminus of the small subunit acts as the catalytic nucleophile in Escherichia coli and Helicobacter pylori GGT (15,16). Using mass spectrometry analysis of inhibitor-bound hGGT1, Castonguay et al (17) identified Thr-381 as the catalytic nucleophile in the human enzyme.…”
mentioning
confidence: 99%
“…It is thought to play key roles in glutathione metabolism in both prokaryotic and eukaryotic organisms. Since its discovery in the sheep kidney, 1) it has been isolated and characterized from various sources such as humans, 2) rats, 3) radishes, 4) fungi, 5) Escherichia coli, 6) Helicobacter pylori, 7) and Bacillus subtilis.…”
mentioning
confidence: 99%
“…However, T398S H. pylori GGT was still able to autoprocess into and subunits, although the t 1/2 for processing was increased 1.4-fold. In contrast, T342A HpxW did not autoprocess (data not shown; Boanca et al, 2007).…”
Section: Active-site Comparisonmentioning
confidence: 87%
“…GGT is a relatively recent addition to the Ntn-hydrolase superfamily (Suzuki & Kumagai, 2002). Many members of the Ntn-hydrolase superfamily have been structurally characterized, including B. subtilis glutamine 5-phosphoribosyl-1-pyrophosphate amidotransferase (Smith et al, 1994), E. coli penicillin G acylases and the E. coli, H. pylori and B. subtilis GGTs (Boanca et al, 2007;Okada et al, 2006;Wada et al, 2010). BLAST results suggested that HpxW is a member of the GGT family, which has modest sequence identity among its members ($30%; Suzuki et al, 1989).…”
Section: Comparison Of Hpxw To Other Enzymesmentioning
confidence: 99%
See 1 more Smart Citation